Wspólne orędzie Kościoła Rzymskokatolickiego w Polsce oraz Rosyjskiego Kościoła Prawosławmego i jego znaczenie dla stosunków polsko-rosyjskich - Dębowski, Tomasz (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2013)
The „Joint Message to the Nations of Poland and Russia” signed in Warsaw on the17th of August 2012 is the first joint document in the history of the Roman Catholic Church in Poland and the Russian Orthodox Church. The reference to problems left over from the previous centuries in the Polish-Russian relations is conveyed in a compromise form approved by both parties. As they note, the aim of the Joint Message was, inter alia, to initiate the reconciliation process between the Poles and the Russians. The proposal of the Churches arose interest among politicians, intellectuals and mass media. The signing of the Joint Message raised questions not only about future of the Polish-Russian relations but also about the impact of this event on the shape of the Polish political scene, especially in the context of the Smolensk plane crash.
Keywords: Polityka Wschodnia; Ukraina; Federacja Rosyjska; Unia Europejska; NATO; relacje polsko-ukraińskie; stosunki polsko-rosyjskie; Kościół katolicki; kościół prawosławny; dyplomacja publiczna; bezpieczeństwo